Fabrication and electrochemical hydrogen storage performance of Ti49Zr26Ni25 alloy covered with Cd/Pd core/shell particles. (20th September 2019) - Liu, Heng; Tan, Liyuan; Guo, Yalan; Chen, Peng; Gao, Shang; Su, Zhongmin; Liu, Wanqiang; Zhao, Jianxun
Abstract: A facile two-step reduction method is employed to obtain the Cd/Pd core/shell particles. Mechanical alloying and subsequent annealing are used to fabricate the Ti49 Zr26 Ni25 quasicrystal. Composite materials of Ti49 Zr26 Ni25 mixed with different contents of Cd/Pd particles are obtained via ball-milling. The electrochemical performance and kinetics properties of the alloy electrodes for Ni/MH secondary batteries are studied. Ultimately, a maximum discharge capacity of 272.9 mA h/g is achieved for 7% additive content of Cd/Pd. Ti49 Zr26 Ni25  + Cd/Pd shows higher capacity than Ti49 Zr26 Ni25  + Pd (246.8 mA h/g) and original Ti49 Zr26 Ni25 (212.5 mA h/g). Moreover, the composites also exhibit improved cyclic stability and high-rate dischargeability. The Cd/Pd particles with special core/shell microstructure can enhance the electro-catalytic activity of Pd. The Cd/Pd material covered on the surface of alloy can further decrease the charge-transfer resistance and accelerate the hydrogen transmission, thus improving the electrochemical properties and reaction kinetics of the electrode. Highlights: A facile two-step reduction method is used to prepare Cd/Pd core/shell particles. Ti49 Zr26 Ni25 alloy doped with Cd/Pd material is fabricated via ball-milling. The Cmax, cycle stability and HRD of the composite electrode are improved. The Cd/Pd particles can further enhance the electro-catalytic activity of Pd.